Teachers’ And Principals’ Understanding Of Steam In Early Childhood Education Under The Merdeka Curriculum: A Case Study - Putri, Tata Antarisa; Pasiningsih, Pasiningsih (THUFULA, 2026)
The successful implementation of Science, Technology, Engineering, Arts, and Mathematics (STEAM) in early childhood education (ECE) depends on the extent to which those who are involved understand their roles. This study aimed to explore the understanding of STEAM learning among a kindergarten teacher and a school principal in an ECE setting implementing the Merdeka Curriculum. Using a qualitative research, data were collected through classroom observations, in-depth interviews, and document analysis at a kindergarten in Pati Regency, Central Java. Data were analyzed using the Miles and Huberman model. The findings revealed differences in participants’ understanding of STEAM, particularly in science, technology, and mathematics. The teacher tended to view science as observation, technology as electronic devices, and mathematics as number recognition, whereas the principal demonstrated more broader understanding. These differences influenced classroom practices, which remained largely teacher-centered and provided limited opportunities for children’s exploration, critical thinking, and creativity. The study highlights the importance of strengthening teachers’ understanding of STEAM and the role of school’s leader in guiding teacher in implementing STEAM learning in ECE.